Here's the question you clicked on:
AEB047
How do you do 3x+3y+z 5x+2y+2z=7 3x-2y+3z=-9 for x,y,z?
They are a system of equations. First, find the value of one of the variables, say, x, relative to another variable, like if I had \[y = 3x+4\] and \[y = 8x -3\] the first one would become \[x= \frac{ y-4 }{ 3 }\] and then you substitue that x value into the second equation, making it \[y = 8(\frac{ y-4 }{ 3 }) - 3\] Now you can solve for y. Similarly, these equations you also solve for x, y and z, but here, for the first equation, the equation doesn't equal anything. I think you should fix it.